The Importance of History in an MPH Program: A Qualitative Evaluation of an Applied History of Public Health Course. (December 2022) - Talley, Colin L.; Comeau, Dawn L.; German, Taylor; Boykin, Briana; Walker, Elizabeth Reisinger
Historical analysis is a vital but underutilized tool for analyzing and teaching public health and health promotion. An applied history of public health course, designed to meet a Council on Education for Public Health (CEPH) competency and learning objective, was qualitatively evaluated to determine the extent to which the course shaped students' and alumni's views on public health values, identities, and practices. A second aim examined the course's impact on students' and alumni's public health work and their ability to discuss structural biases, inequities, and racism and health. Semi-structured interviews were conducted with 12 alumni and 11 students. Data were analyzed using thematic analysis. The four main themes were the importance of history as foundational knowledge and for the development of professional identities; history as a means to understand race, racism, and the social determinants of health; self-reflection and critical thinking as public health practices and the relevance of history to community health promotion; and the effectiveness of multiple pedagogical techniques. Findings suggest that a course including the history of public health institutions, concepts, practices, and health equity can be a valuable tool to teach students about the social determinants of health, health equity, and racism and health, gain perspective on current health problems, improve critical thinking skills and self-reflection as public health practices, and develop a professional identity. We recommend that MPH programs include a history of public health course and/or incorporate historical perspectives in existing courses. This training is increasingly important to prepare students to promote health equity.